Insights into the Genetic Connectivity and Climate-Driven Northward Range Expansion of Turbo sazae (Gastropoda: Turbinidae) Along the Eastern Coast of Korea - Young-Ghan Cho; Kyungman Kwon; Hyun Soo Rho; Won-Gi Min; Hee-Do Jeung; Un-Ki Hwang; Yong-Kyun Ryu; Areumi Park; Hyun-Ki Hong; Jong-Seop Shin; Hyun-Sung Yang (Animals)
Turbo sazae, a commercially and ecologically significant marine gastropod traditionally found in Jeju Island and the southern coast of Korea, is experiencing a reported northward expansion into the East Sea, likely influenced by rising seawater temperatures. This study provides preliminary genetic insights into the genetic structure and connectivity of T. sazae populations between Jeju and the East Sea using mitochondrial COI sequences. Samples from 6 geographically distinct locations were analyzed, with three cloned replicates generated to enhance sequence reliability. Genetic diversity, haplotype distribution, and population differentiation were then assessed. Our analysis reveals potential genetic connectivity between Jeju and East Sea populations, possibly driven by larval dispersal via the Kuroshio and Tsushima Currents, highlighted by the predominance of shared haplotype EJ1 (60.0% in Jeju, 50.0% in East Sea). Bayesian phylogenetic analysis estimated the time to the most recent common ancestor (MRCA) between Jeju and East Sea populations at approximately 9.7 to 23.3 million years ago, indicating ancient divergence rather than very recent separation. Pairwise FST values and AMOVA results showed generally low levels of genetic differentiation. Given the small sample sizes and use of a single mitochondrial marker, these findings should be interpreted cautiously as preliminary evidence. Nevertheless, this study highlights the need for continued genetic monitoring of T. sazae populations under climate-driven range shifts and provides a foundation for future research incorporating broader genomic approaches.